The features of laser forming of sheet materials - Кагляк, Олексій Дмитрович; Гончарук, Олексій Олександрович; Головко, Леонід Федорович; Лутай, Анатолій Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The mechanisms of laser forming are analyzed. The results of experimental researches are presented. The recommendations for the treatment of carbon steel 65G and stainless steel 12Kh18N10T are presented